The role of black oak woodlands (Quercus pyrenaica Willd.) in small ruminant production in Northeast Portugal - Castro, Marina (2011)
The use of black oak woodlands (Quercus pyrenaica Willd.) by small ruminant flocks was investigated in the northeast Portugal. In their daily grazing itineraries, the animals crossed a large and heterogeneous set of vegetation patches, returning to their corrals every night. Two goats’ flocks and two sheep’ flocks led by shepherds were monthly surveyed from May 1999 to May 2000. A hand rover Global Position System (GPS), recording time, geographical position and land cover, monitored shepherding paths every two minutes. The utilization of black oak woodlands was analyzed by three different approaches: 1) time spending by the flocks at black oak woodlands in relation to total time of itineraries, 2) relation of time spending at black oak woodlands and the crossing length of it, and 3) the contribution of black oak in the diets. GPS data revealed changes in black oak woodlands utilization among seasons and/or kind of flocks. Diet estimation indicated also differences in the intensity and sort of black oak woodlands consumption related to kind of animal and season in the course of the year.